Zwischen Psyche und Gehirn - Fuchs, Thomas (Der Nervenarzt, 2017)
Since its development around 1800 psychiatry has been oscillating between the poles of the sciences and the humanities, being directed towards subjective experience on the one hand and towards the neural substrate on the other hand. Today, this dualism seems to have been overcome by a naturalism, which identifies subjective experience with neural processes, according to Griesinger’s frequently quoted statement “mental diseases are brain diseases”. The progress achieved by the neurobiological paradigm on the level of a fundamental science is in contrast to the tendency to isolate mental illnesses from the patients’ social relationships and to neglect subjectivity and intersubjectivity in their explanation. What should be searched for is therefore an overarching paradigm that is able to establish psychiatry as a relational medicine in an encompassing sense: as a science and practice of biological, psychological and social relationships and their disorders. Within such a paradigm, the brain may be understood and investigated as the central “relational organ” without reductionist constrictions.